2008
DOI: 10.1111/j.1600-0668.2008.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dissatisfaction with the indoor environment in open-plan offices: an analysis of COPE field study data

Abstract: We have demonstrated statistically significant relationships between indoor environment conditions in office spaces and environmental dissatisfaction risk. Although generally supported by prior research, not all of these risk factors are reflected in existing recommended practice documents for office design. Consideration of these findings in future revisions of such documents may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The current situation is far from ideal and the potential for improving the indoor environment is high." In a similar vein, Zweers et al [2] found that lower levels of indoor climate complaints were associated with higher job satisfaction and the authors of the COPE Study [3] noted that "For knowledge workers, job satisfaction is likely a far more important predictor of organizational success", with Veitch et al [4] going so far as to assert that "… these findings, and others reveal that a satisfactory physical environment is one component of a satisfied workforce and an effective organization. "…”
Section: Introductionmentioning
confidence: 81%
“…The current situation is far from ideal and the potential for improving the indoor environment is high." In a similar vein, Zweers et al [2] found that lower levels of indoor climate complaints were associated with higher job satisfaction and the authors of the COPE Study [3] noted that "For knowledge workers, job satisfaction is likely a far more important predictor of organizational success", with Veitch et al [4] going so far as to assert that "… these findings, and others reveal that a satisfactory physical environment is one component of a satisfied workforce and an effective organization. "…”
Section: Introductionmentioning
confidence: 81%
“…Overall environmental satisfaction in turn predicted job satisfaction in a positive relationship (Veitch et al, 2007) (see Figure 2). Other aspects of the COPE research elucidated relationships between the physical environment and satisfaction with lighting, ventilation, and privacy & acoustics Veitch et al, 2003;Veitch et al, 2005;Newsham et al, 2008). Several other studies have shown a significant positive link between the indoor environment, environmental satisfaction and aspects of job satisfaction (e.g.…”
Section: Environmental Satisfactionmentioning
confidence: 99%
“…There is much evidence that better indoor environments do lead to such positive outcomes (e.g. Newsham, Veitch, & Charles, 2008;Newsham et al, 2009;Singh, Syal, Grady, & Korkmaz, 2010;Thayer et al;, and some evidence that building tenants believe green buildings to be beneficial (PRNewswire, 2010).…”
Section: Introductionmentioning
confidence: 99%